Enhancing Professional Development for Science Teachers in Selected Elementary Schools in Suakoko Town, Bong County, Liberia - Forkpah, Eric (Journal of Information System and Education Development, 2024)
This paper probes into the multifaceted issues surrounding violence against women and challenges to girls' education in Liberia. Coomaraswamy's 2002 research underscored the role of cultural behaviors in family structures contributing significantly to violence against women. King and Winthrop's 2015 study explored factors such as poverty, gender norms, and cultural expectations, contributing to discussions on fair educational opportunities. Cunningham et al.'s 2023 research delved into gender disparities across economic, educational, healthcare, and political spheres, employing a women's empowerment perspective. Theoretical frameworks rooted in gender and social norm theories were employed to understand the impact of cultural identity on preschool girls' education in Liberia. The study focused on evaluating negative effects on preschool girls in Bong, Lofa, and Nimba counties, emphasizing the need for targeted interventions to create a supportive environment. Coomaraswamy's 2002 insistence on rejecting the use of cultural considerations to justify violence against girls resonates globally. The study also highlighted disparities in girls' primary school enrollment rates in the region compared to the global average, emphasizing the urgency of addressing educational inequalities. Overall, this paper contributes valuable insights for policymakers, educators, and communities, advocating for positive change in Liberia's educational landscape and women's empowerment.